Management of Infection by Parasitic Weeds: A Review - Mónica Fernández-Aparicio; Philippe Delavault; Michael P. Timko (Plants, 2020)
Parasitic plants rely on neighboring host plants to complete their life cycle, forming vascular connections through which they withdraw needed nutritive resources. In natural ecosystems, parasitic plants form one component of the plant community and parasitism contributes to overall community balance. In contrast, when parasitic plants become established in low biodiversified agroecosystems, their persistence causes tremendous yield losses rendering agricultural lands uncultivable. The control of parasitic weeds is challenging because there are few sources of crop resistance and it is difficult to apply controlling methods selective enough to kill the weeds without damaging the crop to which they are physically and biochemically attached. The management of parasitic weeds is also hindered by their high fecundity, dispersal efficiency, persistent seedbank, and rapid responses to changes in agricultural practices, which allow them to adapt to new hosts and manifest increased aggressiveness against new resistant cultivars. New understanding of the physiological and molecular mechanisms behind the processes of germination and haustorium development, and behind the crop resistant response, in addition to the discovery of new targets for herbicides and bioherbicides will guide researchers on the design of modern agricultural strategies for more effective, durable, and health compatible parasitic weed control.